“Baboons on the road again”: Survey of vehicle occupants on a road crossing a national park in Uganda - Jovia Nabuule; Fantine Benoit; Louise Robinet; Peter Isingoma; David Mwesigye Tumusiime; Harold Rugonge; Sabrina Krief; Odile Petit; Audrey Maille (Revue de Primatologie)
Infrastructures such as roads or railways fragment the forests, but they are also places of encounter between humans and wildlife. Some populations of primates, especially macaques and baboons, are regularly seen on roadsides. As these primates are also involved in direct conflict with humans for access to space and food, it is of particular importance to understand the attitudes of vehicle occupants towards these primates. In this exploratory study, we interviewed 383 vehicle occupants travelling on an asphalt road crossing Kibale National Park, Uganda, to assess how people perceive Olive baboons (Papio anubis) that are regularly present on the road, and the road regulations aiming to protect them (and other animal species). In addition, we daily monitored the road sides to record leftovers of anthropogenic food and to census the vehicles passing by. Most of the respondents did not express any negative attitudes toward baboons, although these primates regularly visit fields and gardens to forage on crops in the area. Few people were concerned about the ‘do not litter’ regulation. Although road users rarely feed them, baboons seem to remain attracted to the road because littering is very common. We recommend more sensitization of road users about the increased risks of accidents when baboons are attracted to the road because of anthropogenic food.